REWARD AND PUNISHMENT PROJECT APPROACH: Model development and pilot study - Abdul Rahman (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2017)
Tax sanctions are vital for tax system to ensure tax laws to be obeyed. Despite the importance of tax sanctions, low feedbacks and law enforcement may limit the effectiveness of a tax system and reducing trust on the government. Therefore, the role of public officials in law enforcement is important. However, studies related to the role of tax sanction and public official are dearth. One of them is the study focusing taxpayers employed in public sectors. This study highlighted the tax sanction as the lowest assessment and effect on tax compliance. Then, the study conducted recommended the reward and punishment as a notion of other form of tax sanctions. This paper focuses on the development of model of reward and punishment based on the Project Design Matrix (PDM) by the steps involving problem analysis, objective analysis, generating project design matrix. The developed project provides a foundation for government and for future studies regarding reward and punishment in the tax sanction framework.